DNA damage during G2 phase does not affect cell cycle progression of the green alga Scenedesmus quadricauda - Hlavová, Monika; Čížková, Mária; Vítová, Milada; Bišová, Kateřina; Zachleder, Vilém (PloS one, 2011)
DNA damage is a threat to genomic integrity in all living organisms. Plants and green algae are particularly susceptible to DNA damage especially that caused by UV light, due to their light dependency for photosynthesis. For survival of a plant, and other eukaryotic cells, it is essential for an organism to continuously check the integrity of its genetic material and, when damaged, to repair it immediately. Cells therefore utilize a DNA damage response pathway that is responsible for sensing, reacting to and repairing damaged DNA. We have studied the effect of 5-fluorodeoxyuridine, zeocin, caffeine and combinations of these on the cell cycle of the green alga Scenedesmus quadricauda. The cells delayed S phase and underwent a permanent G2 phase block if DNA metabolism was affected prior to S phase; the G2 phase block imposed by zeocin was partially abolished by caffeine. No cell cycle block was observed if the treatment with zeocin occurred in G2 phase and the cells divided normally. CDKA and CDKB kinases regulate mitosis in S. quadricauda; their kinase activities were inhibited by Wee1. CDKA, CDKB protein levels were stabilized in the presence of zeocin. In contrast, the protein level of Wee1 was unaffected by DNA perturbing treatments. Wee1 therefore does not appear to be involved in the DNA damage response in S. quadricauda. Our results imply a specific reaction to DNA damage in S. quadricauda, with no cell cycle arrest, after experiencing DNA damage during G2 phase.
Keywords: proteiny buněčného cyklu; Floxuridine; floxuridin; Scenedesmus; poškození DNA; bleomycin; DNA Damage; kofein; DNA Repair; G2 fáze; G2 Phase; Chlorophyta; Cell Cycle Proteins; buněčný cyklus; Cell Cycle; Bleomycin; Caffeine; oprava DNA